Numerical simulation of dynamic and thermal behavior of plasma jet interacting with substrate - Riad Horr; Redha Rebhi; Faouzi Didi; Mohamed Kezrane; Ahmad Alghamdi; Yohannes Tesfaye Zewdie; Enas Ali; Sherif S.M. Ghoneim (Results in Engineering, 2025)
The quality of coating is strongly influenced by the temperature and velocity of the plasma jet. In this study, a two-dimensional axisymmetric numerical model for plasma jet simulation in ANSYS Fluent is developed and presented. An increase in plasma jet velocity and temperature, resulting from the thermal flow from plasma towards the substrate, is the intended outcome of the model. The precision with which two turbulence models, SST-k-ω and RNG-k-ε, generated their respective results was evaluated. The study examined the impact of plasma fluid type, substrate material, and the presence of obstacles on various parameters, including plasma dispersion, gas power, plasma jet temperature and plasma jet velocity. These parameters were analyzed across a range of x-positions. A study on mesh independence, which compared numerical and experimental outcomes, was also presented. The temporal distribution of the substrate was assessed using a transient simulation.